Technical Note: Penumbral width trimming in solid lung dose profiles for 0.9 and 1.5 T MRI‐Linac prototypes. Issue 1 (10th December 2017) - Alnaghy, Sarah J.; Begg, Jarrad; Causer, Trent; Alharthi, Thahabah; Glaubes, Laura; Dong, Bin; George, Armia; Holloway, Lois; Metcalfe, Peter
Abstract : Purpose: Longitudinal magnetic fields narrow beam penumbra and tighten lateral spread of secondary electrons in air cavities, including lung tissue. Gafchromic ® EBT3 film was used to investigate differences between penumbra in solid water and solid lung, without a magnetic field (0 T) and with two field strengths (0.9 and 1.5 T). Methods: The first prototype of the Australian MRI‐linac consisted of a 1.5 T Siemens Sonata MRI and Varian industrial linatron (nominal 4 MV). The second prototype replaced the Sonata with a 1.0 T Agilent split‐bore magnet. Measurements were completed at 0.9 T to maintain the same source‐to‐surface distance between set‐ups. Gammex‐rmi ® solid water with 50 mm of CIRS solid lung inserted as a lung cavity was positioned inside each magnet. This was compared to the same set‐up with solid water only, where film measurements were completed at solid water equivalent depths corresponding to entrance interface/mid/exit interface positions of solid lung from the first set‐up. Multileaf collimator (MLC)‐defined field sizes were set to 3 × 3 cm 2 and 10 × 10 cm 2 . The 80%–20% penumbral width was determined. Results: Under 1.5 T conditions, penumbra narrowing occurred up to 4.4 ± 0.1 mm compared to 0 T. As expected, the effect was less for 0.9 T, which resulted in a maximum narrowing of 2.5 ± 0.1 mm. Exit profile penumbra were more affected than entrance penumbra by up to 2.6 ± 0.2 mm. The 1.5 T field brought the solid water and lung penumbral widths more into alignment by a maximum difference of 0.4 ± 0.1 mm. Conclusions: The trimming of penumbral widths due to magnetic fields in solid water and lung was demonstrated and compared to 0 T. The 0.9 and 1.5 T field trimmed the penumbra by up to 2.5 ± 0.1 mm and 4.4 ± 0.1 mm respectively.